The Influence Of Anemia In Pregnancy With The Incident Of Postpartum Bleeding At Guido Valadares National Hospital Dili Timor Leste - Mafalda Guterres De Carvalho; Atik Setiawan Wahyuningsih; Alfian Fawzi; Dedi Saifulah (Universitas STRADA Indonesia, 2023)
Anemia is a deficiency (deficiency) of red blood cells due to low hemoglobin levels. The lower the mother's hemoglobin level, the greater the risk of postpartum hemorrhage. Objective This study was to analyze the effect of anemia in pregnancy on the incidence of postpartum hemorrhage at the Guido Valadares National Hospital, Dili, Timor-Leste. Method The research used in this research is analytical observational in nature using two independent and dependent variables which require a population of all mothers giving birth, as many as 436 people and some mothers as a sample of 54 people. Instrument study used data from the laboratory, register book, from the Antenatal Book, observation sheets. The tools used are bent, underpad, softex.Analysis The collected data used was processed in a computer system using the SPSS for Windows version 16.0 program which includes univariate and bivariate analysis.Resultsthis research foundp=0,004 <0,05 So this means that there is an influence of anemia in pregnancy on the incidence of postpartum hemorrhage in NASIONAL GUIDO VALADARES. Chi square Value= 0,004 Continuity Correction V=6,509. Conclusion This research shows the influence of anemia in pregnancy on postpartum hemorrhage in HNGV in 2020.